Analysis and quantitative evaluation of temperature influence mechanism of multi-cycle water huff-n-puff in ultra-low permeability reservoirs. (15th January 2023) - Shi, Junjie; Cheng, Linsong; Cao, Renyi; Fang, Jie; Yang, Chenxu; Liu, Gaoling; Du, Xulin
Abstract: Water huff-n-puff technology is an effective method of enhancing oil recovery in ultra-low permeability reservoirs. However, due to the different temperatures between injection water and the reservoir, the water huff-n-puff inevitably causes the change in reservoir temperature, further affecting oil production. Based on the modified embedded discrete fracture model method, this paper proposes a coupled solution framework of temperature field and flow field considering the complex mass transfer and heat transfer mechanism. Compared with the traditional EDFM method, this method has higher calculation accuracy and more complex coupling mechanisms. The influence degree of five thermal influence mechanisms on oil production is quantified and analyzed, including thermal viscosity reduction, thermal expansion, stress sensitivity considering thermal stress, fracture width change, and change of relative permeability curve with temperature. When the injection temperature is lower than the reservoir temperature, the three mechanisms of thermal viscosity reduction, thermal expansion, and the change of relative permeability curve with temperature have significant adverse effects on oil production. The mechanism simplification strategy of the numerical simulation of the actual model is given, which improves the simulation efficiency. The proposed simulation framework and simplification method have reasonable practicability. This work provides a valuable reference for water huff-n-puff. Highlights: An modified EDFM method is proposed considering complex thermal mechanisms. Quantify the influence degree of different injection temperature effects. A simplified approach to complex mechanisms to accelerate simulation.